Columnea caudata and columnea megafolia, two new species of gesneriaceae (2013)
Two new species of Columnea belonging to section Collandra (Gesneriaceae) from the “cordillera Occidental” in the Colombian Andes are described and illustrated. Columnea caudata is distributed along the Biogeographical Chocó in the Departments of Antioquia, Chocó, Risaralda, and Valle del Cauca, whereas Columnea megafolia is restricted to Antioquia, and probably is an endemic species of the National Natural Park Las Orquídeas.